2015
DOI: 10.1136/bmjopen-2015-009521
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of New Zealand retailers’ responses to standardised packaging legislation and tobacco industry opposition

Abstract: ObjectivesMany of the approximately 8000 New Zealand retailers selling tobacco are small stores that tobacco companies have represented as victims of policy measures designed to reduce smoking. Despite this depiction, many retailers experience considerable ambivalence in selling tobacco, a product they know harms their customers. We explored how retailers perceived the proposed introduction of standardised (or ‘plain’) packaging and their assessment of arguments made by tobacco companies in submissions on prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Searches generated ten relevant empirical studies 21,30,[32][33][34][35][36][37][38][39] : three were qualitative studies (two reporting focus group research with young adult smokers in Scotland 30,32 , and in-depth interviews with retailers in New Zealand 39 ); three were content analyses (of online commentary on tobacco packaging in Australia 33 , UK press coverage of the illicit tobacco trade 34 and the four TTC submissions to the consultation in the UK 35 ); two were cross sectional surveys (of illicit tobacco use following introduction of standardized packaging in Australia) 36,37 ; and two were before and after studies (one of availability of illicit tobacco in small retail outlets 38 and one empty-pack survey before and after the introduction of standardized packaging in Australia) 21 . See Table 2 for a summary of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Searches generated ten relevant empirical studies 21,30,[32][33][34][35][36][37][38][39] : three were qualitative studies (two reporting focus group research with young adult smokers in Scotland 30,32 , and in-depth interviews with retailers in New Zealand 39 ); three were content analyses (of online commentary on tobacco packaging in Australia 33 , UK press coverage of the illicit tobacco trade 34 and the four TTC submissions to the consultation in the UK 35 ); two were cross sectional surveys (of illicit tobacco use following introduction of standardized packaging in Australia) 36,37 ; and two were before and after studies (one of availability of illicit tobacco in small retail outlets 38 and one empty-pack survey before and after the introduction of standardized packaging in Australia) 21 . See Table 2 for a summary of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…There were few studies examining tobacco standardized packaging and illicit trade and those that were available were generally not of high quality. We identified ten relevant empirical studies which examined standardized packaging and illicit tobacco 21,30,[32][33][34][35][36][37][38][39] . Five studies reported smokers did not intend to 30,32 or actually 21,36,37 purchase more illicit tobacco following standardized packaging although one 33 suggested a small number of responders to online news felt smokers In 179 (59%) of the shops the secret shopper then asked the retailer about the availability of unbranded, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations